Concise Synthesis of Tryptanthrin Spiro Analogues with In Vitro Antitumor Activity Based on One-Pot, Three-Component 1,3-Dipolar Cycloaddition of Azomethine Ylides to Сyclopropenes - Filatov, Alexander S.; Knyazev, Nickolay A.; Shmakov, Stanislav V.; Bogdanov, Alexey A.; Ryazantsev, Mikhail N.; Shtyrov, Andrey A.; Starova, Galina L.; Molchanov, Alexander P.; Larina, Anna G.; Boitsov, Vitali M.; Stepakov, Alexander V. (Synthesis, 2019)
A simple, efficient and atom-economic method has been developed for the synthesis of complex alkaloid-like compounds with spiro-fused indolo[2,1-b]quinazoline and cyclopropa[a]pyrrolizine or 3-azabicyclo[3.1.0]hexane moieties. We have found that one-pot, three-component 1,3-dipolar cycloaddition reactions allow the desired products to be obtained from various cyclopropene derivatives with tryptanthrin-derived azomethine ylides generated in situ, in good to high yields and excellent diastereoselectivity. The possibility of ylide generation was exemplified by using α-amino acids (l-proline, l-4-thiazolidincarboxylic acid) and simplest peptides (dipeptide Gly-Gly, tripeptide Gly-Gly-Gly). Quantum chemical investigations indicate that the reaction proceeds through the S-shaped azomethine ylide, the interaction of which with cyclopropenes proceeds via a less sterically hindered endo-transition state. The antitumor activity of some of spiro-tryptanthrin derivatives against erythroleukemia (K562), cervical carcinoma (HeLa) and colon carcinoma (CT26) cell lines was evaluated in vitro by MTS-assay.
Keywords: one-pot synthesis; azomethine ylides; 1,3-dipolar cycloaddition; cyclopropenes; tryptanthrin; α-amino acids; peptides